Field evaluation of four widely used mosquito traps in Central Europe - Lühken, Renke; Pfitzner, Wolf Peter; Börstler, Jessica; Garms, Rolf; Huber, Katrin; Schork, Nino; Steinke, Sonja; Kiel, Ellen; Becker, Norbert; Tannich, Egbert; Krüger, Andreas (Parasites & vectors, 2014)
To monitor adult mosquitoes several trapping devices are available. These are differently constructed and use various mechanisms for mosquito attraction, thus resulting in different trapping sensitivities and efficacies for the various species. Mosquito monitoring and surveillance programs in Europe use various types of mosquito traps, but only a few comparisons have been conducted so far. This study compared the performance of four commercial trapping devices, which are commonly used in Europe.
Gesehen am 12.08.2020